Hubungan kebiasaan sarapan dan konsumsi fast food dengan status gizi pada remaja di Sukoharjo, Jawa Tengah - Nurfitriani, Syifa Aulia; Soviana, Elida (Jurnal SAGO Gizi dan Kesehatan, 2025)
Background: Adolescence requires balanced nutrition. Therefore, the role of nutrition in this period is crucial to pay attention to. Breakfast is important for everyone, especially adolescents, before starting daily activities, as 20–25% of the energy requirements can be fulfilled by breakfast. Individuals who are not accustomed to breakfast tend to experience excessive hunger during the afternoon and evening, which leads to the consumption of low-nutrient, energy-dense foods and fast food, ultimately affecting their nutritional status.Objective: This study aimed to analyze the relationship between breakfast habits, fast food consumption, and nutritional status among adolescents in State Senior High School 2 Sukoharjo.Methods: This study employed an observational cross-sectional design. The study subjects were 77 eleventh-grade students of State Senior High School 2 Sukoharjo, Sukoharjo Regency, Central Java, selected through proportional random sampling. The research instruments included anthropometric measurements, a 7-day breakfast habit questionnaire, and a Food Frequency Questionnaire (FFQ). Data were analyzed using Spearman’s rank correlation test.Results: There was a significant relationship between breakfast habits (p = 0.019; r = -0,267) and the frequency of fast food consumption (p = 0.002; r = 0,344) and the nutritional status of adolescents. Breakfast habits and frequency of fast food consumption were found to influence the nutritional status of adolescents.Conclusion: These findings highlight the importance of promoting regular breakfast habits and healthy eating patterns to improve and maintain adolescent health.